Interrogation of a minor victim during the investigation of criminal offenses related to domestic violence - V. P. Gontarenko (Bulletin of Kharkiv National University of Internal Affairs)
The scientific article is devoted to certain aspects directly related to the procedural regulation of the interrogation of minors during the pre-trial investigation of criminal proceedings related to domestic violence. An analysis of international legal acts containing relevant standards in the researched field, provisions of the current criminal procedural legislation of Ukraine, as well as scientific works, whose authors worked on the outlined issue, has been carried out. This is due to the fact that sometimes in such proceedings the only source of evidence is the testimony of minor victims. In such cases, the process of obtaining and evaluating evidence is determined by age, individual psychological and many other characteristics of the interrogated.